Overweight as hypertension risk prediction in bus drivers - doi: 10.4025/actascihealthsci.v35i2.9084 (Acta Scientiarum. Health Sciences, 2013)
Blood pressure (BP) has been currently associated with several risk markers in cardiovascular diseases and excess body weight although there is only slight evidence on the association of Body Mass Index (BMI) with BP in bus drivers. Current analysis verified the association of BMI with BP in bus drivers and the risk of individuals with excess weight within the context of high blood pressure. The sample consisted of 75 bus drivers who had their BMI and BP evaluated. Statistical analysis was descriptive and Pearson correlation and odds-ratio were p < 0.05. A significant relationship between BMI and blood pressure, namely, r = 0.438 (p < 0.05) was evident. Individuals with weight excess weight were 4.04 times more likely to have high blood pressure (p < 0.05). Results showed individuals with excess weight were more likely to develop high blood pressure conditions.